Dinamika Vegetasi pada Petak Permanen Rasamala (Altingia excelsa Noronha) di Bodogol, Taman Nasional Gunung Gede Pangrango, Jawa Barat - Sadili, Asep (Perhimpunan Biologi Indonesia, 2014)
First year re-monitoring conducted in 2009 through measuring the entire individuals that have been given numbersand giving new numbers to individuals with stem diameter more than 5 cm. The result of re-monitoring indicatesthat the numbers of populations and species increased, but not significant. Mortality rate observed 7 individualsper hectare (about 1.20 %); whereas natality rate observed 25 individuals per hectare (about 2.52 %), which isregarded as low. Basal area observed in 2008 was approximately 26.55 m2 per hectare and it increased to about27.34 m2 per hectare in 2009. Total number of individuals in 2009 was 595 individuals from 119 species, 86genera, and 44 families with diversity index of 3.60 (HÃ¢â¬â¢). Elaeocarpus petiolatus (Elaeocarpaceae) and Planchoniavalida (Sapotaceae) are new additions. Altingia excelsa is still the dominant species.Keywords: Forest dynamics, rasamala permanent plots, Bodogol, GPNP